Physicochemical and Structural Characterization of Coffee Husks for Sustainable Applications in Biodegradable Materials - Evelyn Alegria Vivas; Héctor Samuel Villada Castillo; Edier Gaviria Acosta (Journal of Natural Fibers)
The physicochemical and structural characteristics of coffee husks obtained by humid medium were determined, from coffee grown in the municipality of Pitalito, Colombia. For this, the physicochemical characterization was carried out. Among the most significant results was the considerable fiber content of the husks, at around 70%. Of this, 17.86% corresponds to lignin. In light of this and reviewing the other parameters analyzed, it can be established that coffee husks show important and promising structural characteristics for use in the manufacture of biodegradable products, in addition to highlighting the content of microelements such as potassium, calcium, phosphorus, and magnesium, which can further serve to encourage their use.